PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT PADA MATA PELAJARAN GEOGRAFI - Jamallian Asri; Pargito Pargito; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2013)
This research is a quasi experimental study aimed to determine the application of cooperative learning model Teams Games Tournament in improving student achievement. Design used in this study is a one-group pretest-posttest design. The population in this study were all students of class XI IPS SMA Negeri 1 Natar South Lampung school year 2012/2013. The research sample XI IPS 4 of four classes by simple random sampling. Based on the results of the data analysis we concluded that student achievement is better after using cooperative learning model TGT, seen from keefetifitasannya of student achievement after such treatment an effective learning model is used to improve student achievement geography class XI semester IPS SMA Negeri 1 Natar South Lampung school year 2012/2013 in the matter distribution of flora.Kata kunci: pembelajaran kooperatif tipe teams games tournament, prestasi belajar, efektititas belajar